Analysis of Municipal Solid Waste Collection Methods Focusing on Zero-Waste Management Using an Analytical Hierarchy Process - Apaydin, Omer; Han, Gul Sumeyra Akcay (MDPI, 2023)
The need to transition from a consumption-based waste hierarchy to a resource-conserving zero-waste management system for sustainable resource management has become unavoidable in today's world. In this study, five different methods for waste separation at source were analyzed using an analytical hierarchy process based on five commonly used waste disposal methods. As a result of the analytical hierarchy analysis, ratios of 0.347, 0.286, 0.200, 0.101, and 0.066 were obtained for the five separation methods (0.347 for separation with six-parameter separate collection and 0.101 for mixed waste collection). The ratio of 0.286, achieved for the triple-separation method, was chosen to meet the requirements of the zero-waste regulation in Turkiye, and a district in Istanbul was selected as the study area. A model based on the residence density was developed. Within the scope of the model, the neighborhoods in the study area were statistically divided into three classes. By choosing one neighborhood from each class, route optimizations were made for both the existing routes and triple separations. The Network Analyst function in ArcGIS was used to determine the optimal routes based on the traveling distances and operational times of vehicles associated with each route. The results of the route-based analyses show that carbon dioxide emissions will increase by only 1.15% compared to the current situation, but the total amount will decrease in the long term if all waste management processes are carried out within the scope of zero-waste management.
Keywords: analytical hierarchy process; exhaust emission; route optimization; separation at source; solid waste collection; geographic information system; zero-waste management; GREENHOUSE-GAS EMISSIONS; GIS; TRANSPORTATION; SELECTION; MODEL; QUANTIFICATION; SUSTAINABILITY; SEPARATION; REDUCTION; Science & Technology - Other Topics; Environmental Sciences & Ecology